Pendampingan optimalisasi pengelolaan Badan Usaha Milik Desa Penyengat Olak Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi - Citra Darminto; Haryadi Haryadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The assistance in the management of Village-Owned Enterprises aims to provide input on constraints faced by the village government to achieve the management of Village-Owned Enterprises (BUMDes) that have not been optimal. In accordance with law No. 6 of 2014, that villages are given the authority to carry out the administration of government in accordance with the interests of the village community. Village authority has been granted based on village propositions which cover government affairs provided by the district / city that have been submitted to the village. Villages have an obligation to provide governance that aims to prosper their society. In order to achieve this, the Village Original Income (PADes) was also supported to strengthen the village economy, through strengthening BUMDes that sided with the institution in optimizing Village Original Income. Inaccessibility of Village Original Income (PADes) occurs due to the lack of role of BUMDes. It also has an impact on society in strengthening the economy of the community. This is what happened in Penyengat Olak Village, jambi sub-district outside the city of Muaro Jambi district, which caused it to be unable to be independent in various aspects. Therefore, the existence of socialization in community service is expected to provide a better impact and solutions in solving the problems that occur and aim to explore the potential of the village in the context of sustainable community empowerment.